2014
DOI: 10.1371/journal.pone.0110613
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of FLOWERING LOCUS T-Like Gene in Alternate Bearing ‘Hass' Avocado Trees Suggests a Role for PaFT in Avocado Flower Induction

Abstract: In many perennials, heavy fruit load on a shoot decreases the ability of the plant to undergo floral induction in the following spring, resulting in a pattern of crop production known as alternate bearing. Here, we studied the effects of fruit load on floral determination in ‘Hass' avocado (Persea americana). De-fruiting experiments initially confirmed the negative effects of fruit load on return to flowering. Next, we isolated a FLOWERING LOCUS T-like gene, PaFT, hypothesized to act as a phloem-mobile florige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 51 publications
7
58
0
3
Order By: Relevance
“…) and avocado (Ziv et al . ), flower induction in olives occurs at a time when, normally, no fruit are present on the tree. The nature of this ‘biochemical memory’ is unknown to us, yet its outcome may be through OeFT and OeTFL1‐1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) and avocado (Ziv et al . ), flower induction in olives occurs at a time when, normally, no fruit are present on the tree. The nature of this ‘biochemical memory’ is unknown to us, yet its outcome may be through OeFT and OeTFL1‐1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet tested in olive, in other fruit trees, there is growing evidence that HFL directly inhibits flower induction (Nakagawa et al 2012;Nishikawa et al 2012;Samach and Smith 2013;Ziv et al 2014;Haberman et al 2016). In any case, in olive, a branch with HFL will not initiate inflorescences the following winter and will thus carry no fruit the following summer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroboration of these results using further model plant systems, for example rice, would increase support for the generality of these gene functions and support the argument that these loci have similar functions in palms. However, it has already been shown that much of the core flowering time control system is conserved across widely diverged species, with measurable phenotypic effects as a result of transferring genes from monocot to dicot (rice to potato; Navarro et al ., ), perennial to annual and vice versa ( Arabidopsis to and from Populus ; Peña et al ., ), tropical to temperate (avocado to Arabidopsis ; Ziv et al ., ), and photoperiodic to nonphotoperiodic species (tomato to Arabidopsis ; Ben‐Naim et al ., ). There is more interspecific variation in abiotic stress responses, but there are still numerous conserved genes and pathways for drought and salinity tolerance between taxonomically diverse groups such as angiosperms and bryophytes (Cuming et al ., ; Pareek et al ., ; Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently these hypotheses have been overtaken by the demonstration that in the years "on" the fruit suppresses the expression of the gene ortholog FLOWERING LOCUS T, PaFT (Ziv et al, 2014) from the end of October to the end of November, and only in the buds of the trees "off" is an expression of the floral identity transcripts PaAP1 and PaLFY, with significant variations detected since…”
Section: Alternate Bearingmentioning
confidence: 99%